Management of traditional risk factors for the development and progression of chronic kidney disease - Lo, Robin; Narasaki, Yoko; Lei, Sean; Rhee, Connie M (Clinical kidney journal, 2023)
Chronic kidney disease (CKD) and its downstream complications (i.e. cardiovascular) are a major source of morbidity worldwide. Additionally, deaths due to CKD or CKD-attributable cardiovascular disease account for a sizeable proportion of global mortality. However, the advent of new pharmacotherapies, diagnostic tools, and global initiatives are directing greater attention to kidney health in the public health agenda, including the implementation of effective strategies that (i) prevent kidney disease, (ii) provide early CKD detection, and (iii) ameliorate CKD progression and its related complications. In this Review, we discuss major risk factors for incident CKD and CKD progression categorized across cardiovascular (i.e. hypertension, dyslipidemia, cardiorenal syndrome), endocrine (i.e. diabetes mellitus, hypothyroidism, testosterone), lifestyle (i.e. obesity, dietary factors, smoking), and genetic/environmental (i.e. CKDu/Mesoamerican nephropathy, APOL1, herbal nephropathy) domains, as well as scope, mechanistic underpinnings, and management. Lay Summary In this Review, we discuss major risk factors for incident chronic kidney disease (CKD) and CKD progression categorized across cardiovascular (i.e. hypertension, dyslipidaemia, cardiorenal syndrome), endocrine (i.e. diabetes mellitus, hypothyroidism, testosterone), lifestyle (i.e. obesity, dietary factors, smoking), and genetic/environmental (i.e. CKDu/Mesoamerican nephropathy, APOL1, herbal nephropathy) domains, as well as scope, mechanistic underpinnings, and management.